Argon–Helium Cryoablation for Cutaneous Squamous Cell Carcinoma in the Elderly - Huang, Qianwen; Xu, Wenshen (Frontiers in Oncology, 2022)
Cutaneous squamous cell carcinoma (cSCC) is a common type of malignant neoplasm in non-melanoma skin cancer (NMSC). Most cases of simple cSCC are considered curable by surgical removal of the lesion. However, clinical treatments for cSCC with medium- or large-sized lesions are difficult. Meanwhile, the effectiveness of the treatments is not guaranteed, especially for elderly patients, because of an intolerance to surgical resection or other adjuvant modalities. In such cases, safe and effective treatments with excellent aesthetic outcomes are urgently needed. In this study, we reported 6 elderly cSCC patients with medium- or large-sized lesions treated with argon–helium cryoablation. The average age of all 6 patients was 78 years (range 72–85 years). They were all diagnosed with cSCC with a median tumor size of 5.8 cm (range 2.5–15.5 cm) and dermal invasion. Complete ablation was achieved in all cases after a single ablation session (2 freeze–thaw cycles). Patients experienced mild pain and hemorrhage after ablation, but the symptoms were manageable. One patient developed infection and fever because of extensive necrosis of the tumor, which was eventually cured after treatment. All patients obtained good cosmetic outcomes, and their quality of life improved significantly. In the 5-year follow-up study, 4 patients were alive while 2 patients died of unrelated diseases 3 years after cryotherapy. None of the 6 patients had a recurrence. These results suggested the feasibility of argon–helium cryoablation as a novel therapeutic strategy for elderly cSCC with medium- or large-sized lesions.